2004
DOI: 10.1118/1.1738960
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of an iterative, linear segmentation routine into a mammographic mass CAD system

Abstract: In previous research, we have developed a computer-aided detection (CAD) system designed to detect masses in mammograms. The previous version of our system employed a simple but imprecise method to localize the masses. In this research, we present a more robust segmentation routine for use with mammographic masses. Our hypothesis is that by more accurately describing the morphology of the masses, we can improve the CAD system's ability to distinguish masses from other mammographic structures. To test this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…To investigate the effect of the FCLAHE over the accuracy of the subsequent segmentation algorithm, we performed the Catarious segmentation method (CSM) to delineate the masses [14]. We performed CSM segmentation method on both the original images and the enhanced images using either CLAHE or FCLAHE.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effect of the FCLAHE over the accuracy of the subsequent segmentation algorithm, we performed the Catarious segmentation method (CSM) to delineate the masses [14]. We performed CSM segmentation method on both the original images and the enhanced images using either CLAHE or FCLAHE.…”
Section: Resultsmentioning
confidence: 99%
“…The filtered image was first thresholded at the 99th percentile. The threshold continued to be lowered to each lower percentile to grow regions until the entire region was segmented or a region attempted to merge with another suspicious region [16] . A minimal rule-based false-positive approach was used to eliminate suspicious regions based on area and eccentricity.…”
Section: Image Processingmentioning
confidence: 99%
“…Improper use of these methods can lead to significant biases in the estimated performance levels. We reviewed all research articles on the development and evaluation of CAD schemes that were published in Medical Physics [15][16][17][18][19][20][21] and IEEE Transactions on Medical Imaging [22][23][24] in 2004. We found that, among the 10 papers we reviewed, nine employed incorrect evaluation methods leading to increased bias and/or variance in the estimated performance levels [9].…”
Section: Discussionmentioning
confidence: 99%